Effect of a mixture of Centellaasiatica and Ginger on skin wound of cat - BouftiraIbtissem, Dr; KyawZar, Aung (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
The present study shows the effect of a mixture of C.asiatica and Z.officinale (Ginger). The plants powder was applied on injured cat skin caused by accident, with a proportion of 5g of each plant powder. After one week of treatment, the diameter of the wound skin decreases from 4 to 2 cm. The wound disappear totally after two weeks. The result can be explained by the effect of Asiaticoside (triterpene glycoside) present in C. asiatica powder on the wounded skin. The ginger act by its anti-inflammatory effect, the powder contains inhibitors against prostaglandin biosynthesizing enzyme (PG synthetize).